Applying agency theory and resource dependence theory to identify determinants and impacts of voluntary web disclosure quality on the information asymmetry / Indah Melati - Melati, Indah (2022)
A more complex and dynamic global market has forced companies to be more transparent by providing disclosure information based on usefulness and relevance to all stakeholders. The inherently advanced features of websites make web disclosure a more useful means of disclosing corporate information compared to traditional annual reports. However, the features are still underutilized. The aim of the present study is twofold. Firstly, it investigates the determinant factors influencing voluntary web disclosure quality, and secondly, it examines the impact of voluntary web disclosure quality. Voluntary web disclosure quality is measured on a comprehensive web disclosure index of 47 items capturing both the content and presentation dimensions. The content dimension counts the variety and richness of the information disclosed by drawing on semantic properties. Using an OLS regression framework with the top 100 Indonesian-listed companies in 2020, it was found that family ownership and BOD education level have negative effect on voluntary web disclosure quality. Conversely, government ownership, BOC internationalization, and BOD accounting experts can significantly improve voluntary web disclosure quality. Further, this study affirms that higher voluntary web disclosure quality is related to a lower level of information asymmetry. The result of this study provides insights for regulators to evaluate and conduct some measures to enhance voluntary web disclosure quality. This study contributes to the pieces of literature on corporate disclosure by investigating determinant factors and the impact of voluntary web disclosure quality in a two-tier governance system using two theoretical perspectives, namely agency theory, and resource dependence theory.